Texture and stress transmission in binary granular composites: Comparison between simulations and existing experiments - Pawarut Jongchansitto (2018)
The morphology of two-dimensional cohesionless composite granular media obtained from thermoelastic stress analysis (TSA) experiments and molecular dynamics (MD) simulations is methodically compared by using the statistical analysis through the distributions of the hydrostatic stress in the particles and of the geometrical contact orientation between particles. Two different particles with a stiffness ratio of four between them are employed to prepare the numerical composite samples under study. Under a confined vertical compression in static conditions, experimental and numerical results are in good agreement in terms of the distributions of the hydrostatic stresses and of the contact directions.